Pengaruh Capital Adequacy Ratio dan Suku Bunga Kredit serta Dana Pihak Ketiga Terhadap Non Performing Loan Pada Bank Umum Non Devisa Periode 2011-2014 - Ahyani Nhara; Djoko Setyadi; Musdalifah Azis (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This research aim to analyze of how big influence Capital Adequacy Ratio (CAR), Loan Interest Rate and Third-Party Funds to Non Performing Loan (NPL). The Population in this research are 120 commercial banks in Indonesia period 2011-2014. The Sampling technique used is purposive sampling with certain criteria, so that obtained sample of 28 non-foreign public bank. The analysis technique used is multiple linear regression and hypothesis test using T-test and F-test with level of significance 0,05. Before tested by multiple linear regression test, testified with classical assumption test first to the normality of data test. The results showed that the CAR had no significant negative effect on NPL, Loan Interest Rate had no significant positive effect on NPL and Third-Party Funds had significant positive effect on NPL. The result of determination coefficient shows that 45,8% change of NPL variable can be explained by CAR, Loan Interest Rate and Third-Party Funds, while the rest 54,2% is influenced by other independent variable not included in this research model. Keywords: Capital Adequacy Ratio, Loan Interest Rate, Non Performing Loan,      Third-Party Funds.